Study of organic micropollutants degradation by atmospheric pressure plasma - Phang, Sheng Shan; Cha, Kai Quan; Roslan, Muhammad Sufi (2024)
This study is about the removal of organic micropollutants (OMP) by atmospheric pressure plasma as the effect of micropollutants to the environment and living things is severe. The impact of reactive oxygen and nitrogen on OMP is investigated to degrade it. OMP used in this study are methylene blue and phenol. Both samples are going through plasma treatment in a treatment beaker consisting of two electrodes, one at the bottom and another one on the top surface of water sample. The micropollutants are degraded by the reactive free radicals generated by plasma. The treated samples show a decrease in micropollutants after the analysis of Fourier-transform infrared spectroscopy (FTIR) and Ultraviolet–visible spectroscopy (UV-Vis). Moreover, the findings indicates that the plasma treatment has reduced micropollutant concentration, although the micropollutant is incompletely degraded within 30. Therefore, plasma treatment is a reliable method and should be included as one of the the stages for water treatment